2018
DOI: 10.1111/tmi.13119
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen and meglumine antimoniate combined therapy in cutaneous leishmaniasis patients: a randomised trial

Abstract: In the doses and schemes used in this study, co-administration of oral tamoxifen and Sb resulted in higher cure rates in comparison with the standard scheme of treatment, although not to statistically significant levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Four studies evaluated the combination with each of the following intervention/drugs: allopurinol, 23‐26 imiquimod 27‐30 and pentoxifylline 31‐34 . Three studies investigated the trichloroacetic acid 50% (TCA), 35‐37 and the remaining eleven trials evaluated other additional interventions comprising tamoxifen, 38 cimetidine, 39 omeprazole, 40 ketoconazole, 41 terbinafine, 42 paromomycin, 43 granulocyte macrophage colony‐stimulating factor, 44 interferon gamma, 45 honey, 46 dressing 47 and herbal extract 48 . The trials were conducted in endemic CL areas: fifteen studies in Iran, four in Brazil, three in Colombia and Peru and the following countries conducted one study: Guatemala, Syria, Yemen, Pakistan, Afghanistan and U.A.E.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies evaluated the combination with each of the following intervention/drugs: allopurinol, 23‐26 imiquimod 27‐30 and pentoxifylline 31‐34 . Three studies investigated the trichloroacetic acid 50% (TCA), 35‐37 and the remaining eleven trials evaluated other additional interventions comprising tamoxifen, 38 cimetidine, 39 omeprazole, 40 ketoconazole, 41 terbinafine, 42 paromomycin, 43 granulocyte macrophage colony‐stimulating factor, 44 interferon gamma, 45 honey, 46 dressing 47 and herbal extract 48 . The trials were conducted in endemic CL areas: fifteen studies in Iran, four in Brazil, three in Colombia and Peru and the following countries conducted one study: Guatemala, Syria, Yemen, Pakistan, Afghanistan and U.A.E.…”
Section: Resultsmentioning
confidence: 99%
“…Although our study is exploratory, our data suggest that the molecular players involved in the necroptosis pathway might be useful as a target in alternative treatments in combination of immunomodulatory drugs with drugs currently used for human leishmaniasis disease. Many clinical trials studies in endemic area for leishmaniasis have pointed out the benefits of combination treatment using multiple drugs ( Machado et al, 2010 , 2018 ; Brito et al, 2014 ). In addition, RIPK3 inhibitors have not been used in clinical trials addressing inflammatory diseases, including leishmaniasis.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that there is no LV chemotherapy available by oral route in Brazil and considering the global resistance to oral miltefosine in various parts of the world, the present study investigated the effect of oral TMX-NC on parasite burden and on the histopathological characteristics in L. infantum -infected mice and hamsters. Indicated for treatment or prevention of human breast cancer, TMX is used continuously for 5–10 years with daily doses of 10–40 mg/day and shows a good safety profile [ 57 ]. In the literature, doses administered for the experimental treatment of breast tumors in mice range from 45 to 400 mg/kg/day [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our histopathological analysis of the liver and spleen showed that our formulation was able to reduce alterations in these organs. Therefore, the highest doses tested orally in our experimental models of visceral leishmaniasis in mice and hamsters, when transposed to human doses, will be within the range already studied clinically, which was already found not to induce significant adverse effects in patients [ 57 ].…”
Section: Discussionmentioning
confidence: 99%